Bioremediation Using Bacillus subtilis and Saccharomyces cerevisiae to Reduce Chromium in Electroplating Liquid Waste - Mardiyono Mardiyono; Sajidan Sajidan; Mohammad Masykuri; Prabang Setyono (Universitas Sebelas Maret, 2019)
The electroplating industry produces liquid waste containing a small number of heavy metals but is toxic. Wastewater containing chromium (Cr) absorbed into the soil will affect soil fertility. Waste management is needed so that the abiotic and biotic environment is not poisoned by Cr. Bioremediation using bacterial and fungal microbes are applicable to reduce Cr levels in electroplating liquid waste. The purpose of this research was to investigate the reduction level of Cr in electroplating liquid waste through bioremediation using Bacillus subtilis and Saccharomyces cerevisiae. Laboratory experiments were conducted using variations in microbial concentrations (102.5 cells ml-1 and 105 cells ml-1), variations in microbial types (Bacillus subtilis bacteria, Saccharomyces cerevisiae fungi, and mixtures of both microbes), and variations in incubation time (6, 12, and 24 hours). The initial Cr concentration and the results of the bioremediation process were determined by measuring the absorbance and the Cr levels using Atomic Absorption Spectrophotometry (AAS). Based on experiments, the use of Bacillus subtilis 102.5 cells ml-1 with a 24-hour incubation time reach the highest percentage reduction in Cr (88.96%), followed by 12-hours incubation time (84.73%), and 6-hours incubation time (79.21%). Furthermore, the use of a microbial mixture of Bacillus subtilis and Saccharomyces cerevisiae 102.5 cells ml-1 with 6-hours, 12-hours and 24-hours incubation time was able to reduce the levels of Cr respectively by 77.46%; 80.18% and 83.04%. Next, Saccharomyces cerevisiae 105 cells ml-1 with 6-hours, 12-hours, and 24-hours incubation time was able to reduce levels of Cr in a row by 50.17%; 52.35% and 55.63%. The results of this study indicate that the bioremediation process using the microbial Bacillus subtilis and Saccharomyces cerevisiae is proven to reduce the levels of Cr in the electroplating industry wastewater. The highest reduction results were achieved on the use of 24-hour incubation time and the use of Bacillus subtilis with a concentration of 102.5 cells ml-1 at 88.96%.